THE IMPORTANCE OF THE FRUIT AND VEGETABLE SECTOR IN INCREASING THE COMPETITIVENESS OF AGRICULTURE AND THE FOOD INDUSTRY (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses ways to improve the efficiency of fruit vegetable production in Uzbekistan. As a result of the analyzes, the effectiveness of fruit vegetable products grown in the Andijan region was studied.